2020
DOI: 10.1111/jan.14355
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of the effects of global health competency improvement programs on nurses and nursing students

Abstract: AimsTo identify trends in global health competency improvement programs for nurses and to verify their effects.DesignSystematic review and meta‐analysis.Data sourcesArticles published from 2000–2017 in Ovid MEDLINE, Embase, and ProQuest and the Cumulative Index to Nursing and Allied Health Literature database, Cochrane Library, Research Information Sharing Service, DataBase Periodical Information Academic, Korean Studies Information Service System, and National Assembly Library.Review methodsCochrane methods w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Readers are encouraged to delve more deeply into strategies that are appropriate for their individual courses, and links to additional resources are included to stimulate future learning activities. A meta-analysis of global health improvement programs (Kang et al, 2020) suggests that nursing curricula must include information beyond the culture of the client and include socioenvironmental factors, resources, and human rights to meet global health competencies. Students should be prepared to put into practice the interventions that are specific and relevant for individualand population-based care, whether domestic or international.…”
Section: Discussionmentioning
confidence: 99%
“…Readers are encouraged to delve more deeply into strategies that are appropriate for their individual courses, and links to additional resources are included to stimulate future learning activities. A meta-analysis of global health improvement programs (Kang et al, 2020) suggests that nursing curricula must include information beyond the culture of the client and include socioenvironmental factors, resources, and human rights to meet global health competencies. Students should be prepared to put into practice the interventions that are specific and relevant for individualand population-based care, whether domestic or international.…”
Section: Discussionmentioning
confidence: 99%
“…Although professionals may disagree on the specific nursing competencies needed in global health, the undergraduate curriculum must enable nurses to develop international health capabilities (Clark et al., 2016 ), such as the ability to actively respond to domestic and international environmental changes (Lee et al., 2015 ), understanding a patient's culture, disease and health, and possessing knowledge of how increasing GHC is an effective solution for reducing health and medical inequalities (Wilson et al., 2016 ). As a result, a programme is urgently needed to promote the global health competencies among nursing students and meet the needs of international patients from diverse cultural backgrounds (Clark et al., 2016 ; Edwards, 2015 ; Kang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review exploring the effectiveness of a GHC improvement programme for nursing students found that such programmes increased cultural competency and multicultural self‐efficacy among them (Kang et al., 2020 ). Cultural competence is a key factor of healthcare professionals to provide culturally responsive care to people from diverse cultural backgrounds, which is the current need of the hour (Forss et al., 2019 ; Safipour et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations